2022
DOI: 10.3390/molecules27196279
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of PollenAid Plus Soft Gel Capsules’ Hydroalcoholic Extract in Isolated Prostates and Ovaries Exposed to Lipopolysaccharide

Abstract: Pollen extract represents an innovative approach for the management of the clinical symptoms related to prostatitis and pelvic inflammatory disease (PID). In this context, the aims of the present work were to analyze the phenolic composition of a hydroalcoholic extract of PollenAid Plus soft gel capsules, and to evaluate the extract’s cytotoxic effects, in human prostate cancer PC3 cells and human ovary cancer OVCAR-3 cells. Additionally, protective effects were investigated in isolated prostate and ovary spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…These results collectively indicate that the n-hexane extract possesses a moderate level of antioxidant activity. Our findings are consistent with those of Acquaviva and colleagues, who also found that the antioxidant activity of the n-hexane extract was lower than that of other extracts [34]. This implies that the n-hexane extract could be considered for utilization in situations where a moderate degree of antioxidant efficacy is sought, addressing the specific requirements of industrial or research applications.…”
Section: Antioxidant Propertiessupporting
confidence: 92%
See 1 more Smart Citation
“…These results collectively indicate that the n-hexane extract possesses a moderate level of antioxidant activity. Our findings are consistent with those of Acquaviva and colleagues, who also found that the antioxidant activity of the n-hexane extract was lower than that of other extracts [34]. This implies that the n-hexane extract could be considered for utilization in situations where a moderate degree of antioxidant efficacy is sought, addressing the specific requirements of industrial or research applications.…”
Section: Antioxidant Propertiessupporting
confidence: 92%
“…Total phenolic and flavonoid contents of the extracts were determined by colorimetric methods previously described by Acquaviva et al [34] and Llorent-Martínez et al [61], respectively. The Folin-Ciocalteu and AlCl 3 assays were utilized to determine the total phenolic and flavonoid contents, respectively.…”
Section: Total Phenolics and Flavonoids Contentmentioning
confidence: 99%
“…This analytical method highlighted the effects of different altitudes and agronomical practices (Spontaneous vs. Organically Grown) on the chemical profile. NMR metabolomics is a recognised suitable approach for identifying and quantifying the primary and secondary metabolites of plants [45][46][47], as well as for the study of metabolic processes [48].…”
Section: Introductionmentioning
confidence: 99%
“…CGA is a polyphenol molecule with a strong antioxidant effect that is widely present in many diets and liquid drinks. It can eliminate free radicals in the body and plays a preventive and therapeutic role in many diseases, such as diabetes, hypertension (HPT), and atherosclerosis (AS) [ 39 , 40 , 42 , 43 , 44 ]. CGA not only has antioxidant activity but also has a series of biological functions such as liver anti-inflammatory protection and neuroprotection [ 39 , 40 , 41 , 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…It can eliminate free radicals in the body and plays a preventive and therapeutic role in many diseases, such as diabetes, hypertension (HPT), and atherosclerosis (AS) [ 39 , 40 , 42 , 43 , 44 ]. CGA not only has antioxidant activity but also has a series of biological functions such as liver anti-inflammatory protection and neuroprotection [ 39 , 40 , 41 , 42 , 43 , 44 ]. Recent studies have found that CGA also has therapeutic effects on PCOS [ 30 , 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%